A metal–organic framework with rod secondary building unit based on the Boerdijk–Coxeter helix. Issue 77 (5th September 2016) - Xiao, Qiong; Wu, Yuan; Li, Mian; O'Keeffe, Michael; Li, Dan
Abstract : The interplay between local aperiodicity and global periodicity gives rise to an uninodal net for a rod metal–organic framework. Abstract : The renowned aperiodic Boerdijk–Coxeter helix is identified, with a modified, periodic form, in a MOF named ROD-1 [formulated as Cd(L), H2 L = (3, 5-dimethyl-1 H -(pyrazol-4-yl)-methylene)benzoic acid], which exhibits unusual gas adsorption behaviours attributed to guest–guest interactions, and also interesting structural dynamics responding to temperature variation and gas adsorption.